2002
DOI: 10.1109/tmag.2002.803204
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic dynamics of Zn/sup 57/Fe/sub 2/O/sub 4/ nanoparticles dispersed in a ZnO matrix

Abstract: The magnetic properties of diluted ZnFe 2 O 4 nanoparticles with nearly normal spinel structure, dispersed in a nonmagnetic ZnO matrix, are presented. A magnetic transition to an ordered state is observed at about 19 K, from Mössbauer and magnetic measurements. Detailed characterization of the frequency and field dependence shows that, below the magnetic transition, the system displays several features that suggest a collective freezing of ferrimagnetic particles. Although single-domain particles are inferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
7
12
1
Order By: Relevance
“…However, since there is antiferromagnetic interactions both in intra-clusters and interclusters spins, and size (effective moment) distribution of the particles, the resultant overall magnetic behavior would naturally be expected to be considerably different than that of conventional super-paramagnetic systems. This results supports predictions of Oliver and Chinnasamy et al for spin-glass-like behavior for nanosized ZnFe 2 O 4 particles [42][43][44].…”
Section: Magnetic Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…However, since there is antiferromagnetic interactions both in intra-clusters and interclusters spins, and size (effective moment) distribution of the particles, the resultant overall magnetic behavior would naturally be expected to be considerably different than that of conventional super-paramagnetic systems. This results supports predictions of Oliver and Chinnasamy et al for spin-glass-like behavior for nanosized ZnFe 2 O 4 particles [42][43][44].…”
Section: Magnetic Studiessupporting
confidence: 92%
“…It is found that ZFC and FC curves overlap and a peak of magnetization about 19 emu/g at the temperature of 16 K was observed. While in the case of M-T curve with 20 Oe applied field, the peak increases to about 23 K, which is due to the decrease of the interactions among the particles with decreasing applied magnetic field as observed in other studies [46,47].…”
Section: Magnetic Studiessupporting
confidence: 78%
See 2 more Smart Citations
“…In nanoparticles especially below 10 nm the magnetic anisotropy constant increases drastically while decreasing sizes. Large values of K in nanoparticles may be attributed to dipolar interactions for concentrated systems and surface effects mainly in diluted systems [34,35] (Fig. 5).…”
Section: Tem Analysismentioning
confidence: 99%